The Laugh Maker - Curwood, James Oliver, 1878-1927; Hoskins, Gayle Porter, 1887-1962 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Laugh Maker" by James Oliver Curwood is a novel written in the early 20th century. The book tells the story of Bobby McTabb, a man who is known for his cheerful and jovial personality, but who faces a significant life change after leaving his hometown of Fawcettville with a large sum of money obtained unethically. It explores themes of happiness, identity, and redemption, as McTabb's journey leads him through personal transformation and ultimately a quest to regain trust. The narrative follows Bobby McTabb, a rotund and lovable character who becomes the heart of his community in Fawcettville. After winning the townspeople's affection, he unexpectedly absconds with their money, embarking on an adventurous escape that leads him through hardship and self-discovery in the wilderness. As Bobby loses weight and transforms both physically and mentally, he adopts a new persona as J. Wesley Brown. When he reunites with the love interest, Kitty Duchene, he grapples with the truth about his past, leading to a dramatic revelation in a carnival funhouse. In a final act of redemption, he returns to Fawcettville to repay the townsfolk, restoring his relationships and reaffirming the love that binds him to the community he left behind. (This is an automatically generated summary.)
Release date is 2022-01-13
Roger Frank and Sue Clark
Keywords: Short stories; Man-woman relationships -- Fiction; Embezzlement -- Fiction